Effect of Additional Rice Bran and Harvesting Period Againts Pleurotus ostreatus Yield Productivities - Afifah, Qanitatul (University of Brawijaya, 2019)
Percentage of rice bran added (main factor) in oyster mushroom; P. ostreatus growing substrate was 10%,15%, and 20% of total baglog weight. Harvesting period (period 1, periode 2, period 3) became a nested factor on this study. P. ostreatus yield showed that percentage of rice bran added gave significantly different result on P. ostreatus wet weight (rice bran 10% and 15%). Harvesting period showed significantly result on harvesting time, wet weight, and number of fruiting body. The best result were obtained in additional 15% rice bran based of the result comparison with 10% rice bran with 5Â parameter on this study. 15% rice bran added gave the best result with harvesting time (55.00 days), pileus diameter (5.29 cm), wet weight (67.74 g/baglog), number of fruiting bodies (9.67 fruit), and productivity (5.12 g/day).